Targeting PDZ domains as potential treatment for viral infections, neurodegeneration and cancer - Caterina Nardella; Lorenzo Visconti; Francesca Malagrinò; Livia Pagano; Marianna Bufano; Marianna Nalli; Antonio Coluccia; Giuseppe La Regina; Romano Silvestri; Stefano Gianni; Angelo Toto (Biology Direct, 2021)
Abstract The interaction between proteins is a fundamental event for cellular life that is generally mediated by specialized protein domains or modules. PDZ domains are the largest class of protein–protein interaction modules, involved in several cellular pathways such as signal transduction, cell–cell junctions, cell polarity and adhesion, and protein trafficking. Because of that, dysregulation of PDZ domain function often causes the onset of pathologies, thus making this family of domains an interesting pharmaceutical target. In this review article we provide an overview of the structural and functional features of PDZ domains and their involvement in the cellular and molecular pathways at the basis of different human pathologies. We also discuss some of the strategies that have been developed with the final goal to hijack or inhibit the interaction of PDZ domains with their ligands. Because of the generally low binding selectivity of PDZ domain and the scarce efficiency of small molecules in inhibiting PDZ binding, this task resulted particularly difficult to pursue and still demands increasing experimental efforts in order to become completely feasible and successful in vivo.